Republic of Korea : Financial Sector Assessment Program-Technical Note-Technological Change, Legal Frameworks, and Implications for Financial Stability. (IMF Staff Country Reports; Country Report, 2020)
Technological innovation in Korea holds great potential for the deepening of its financial system, that could lead to an increase of product offerings and lowering of transaction costs. Korea's financial sector legal framework, particularly the recently announced open banking initiative and anticipated amendments to the legal frameworks for electronic financial transactions and use of personal data, will play a key role in shaping the direction of innovation and competition in the financial sector. The already highly modernized and digitally connected state of the Korean financial sector will amplify the impact of these changes to market structure and competition. Korea's fintech experience illustrates that even within an already highly technologically advanced, efficient, and inclusive financial sector, significant benefits can still be reaped from innovation in financial services.